Silencing of STE20-type kinase STK25 in human aortic endothelial and smooth muscle cells is atheroprotective - Emmelie Cansby; Sima Kumari; Mara Caputo; Ying Xia; Rando Porosk; Jonathan Robinson; Hao Wang; Britt-Marie Olsson; Josefine Vallin; Julie Grantham; Ursel Soomets; L. Thomas Svensson; et al. (Communications Biology, 2022)
Silencing of STK25, an STE20-type kinase, in human aortic endothelial and smooth muscle cells reduces lipid accumulation and suppresses inflammation and fibrotic pathways, ultimately exerting atheroprotective effects.